2016
DOI: 10.3390/s16101558
|View full text |Cite
|
Sign up to set email alerts
|

ReliefF-Based EEG Sensor Selection Methods for Emotion Recognition

Abstract: Electroencephalogram (EEG) signals recorded from sensor electrodes on the scalp can directly detect the brain dynamics in response to different emotional states. Emotion recognition from EEG signals has attracted broad attention, partly due to the rapid development of wearable computing and the needs of a more immersive human-computer interface (HCI) environment. To improve the recognition performance, multi-channel EEG signals are usually used. A large set of EEG sensor channels will add to the computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(85 citation statements)
references
References 26 publications
2
82
0
1
Order By: Relevance
“…Although the answer to what are the most emotion-relevant EEG features is still under investigation, power features from different frequency bands are still the most popular in the context of emotion recognition. Studies [26,197,218] have shown that power spectral density (PSD) extracted from EEG signals performs well on distinguishing affective states.…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the answer to what are the most emotion-relevant EEG features is still under investigation, power features from different frequency bands are still the most popular in the context of emotion recognition. Studies [26,197,218] have shown that power spectral density (PSD) extracted from EEG signals performs well on distinguishing affective states.…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
“…These proposed systems aim to explore or improve EEG-based emotion recognition systems. [2,39,41,42,49,50,57,61,63,92,104,108,109,117,131,136,149,152,157,173,174,185,186,189,191,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209]217,219,[223][224][225]229,[262][263][264][265][266]<...>…”
Section: Monitoringmentioning
confidence: 99%
“…This resulted in two participants being excluded at this stage. The remaining twenty participants had a mean age of 22 (range [19][20][21][22][23][24][25][26][27][28][29][30]. Nine of these participants were female.…”
Section: Participantsmentioning
confidence: 99%
“…Additionally, it has been shown that a combination of EEG and other physiological signals may be used to identify an individual's affective state when visual stimuli or combinations of visual and auditory stimuli are used [24], [25], [26], [27]. However, neurological responses to affective stimuli differ according to the modality of the stimuli [28], so affective state detection methods designed for visual stimuli may not work as well for musical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…ReliefF is a widely-used feature selection algorithm [34] that carries out the process of feature selection by handling a sample from a dataset and creating a model based on its nearness to other samples in its own class and distance from other classes [35]. This study applies the ReliefF feature selection method to evaluate every feature in comparison to other features and determine which features are more effective in the classification phase.…”
Section: Feature Selectionmentioning
confidence: 99%